Decree No.239 of the year 2018 Promulgating the Executive Regulations of law on Regulating the Gas market Activities = اللائحة التنفيذية لقانون تنظيم أنشطة سوق الغاز / Egypt law legislations. - Egypt. law legislations. (2025)
1. Definitions -- 2. licenses -- 3. Gas market activities -- 4. Networks and facilities usage codes -- 5. Networks and facilities usage tariff -- 6. Separation of activities.